2022
DOI: 10.3389/fnins.2022.991578
|View full text |Cite
|
Sign up to set email alerts
|

The influence of face mask on social spaces depends on the behavioral immune system

Abstract: Interacting with objects and people requires specifying localized spaces where these interactions can take place. Previous studies suggest that the space for interacting with objects (i.e., the peripersonal space) contributes to defining the space for interacting with people (i.e., personal and interpersonal spaces). Furthermore, situational factors, such as wearing a face mask, have been shown to influence social spaces, but how they influence the relation between action and social spaces and are modulated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The influence of Germ Aversion on preferred IPD is in keeping with the findings of Hromatko and colleagues observed during the early stages of the COVID-19 pandemic [ 51 ]. Similarly, Geers and Coello [ 50 ] found that individuals higher in Germ Aversion preferred to keep a greater distance from individuals who were not wearing a face mask. Perhaps surprisingly, the Perceived Infectability dimension turned out not to be a significant predictor of preferred IPD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The influence of Germ Aversion on preferred IPD is in keeping with the findings of Hromatko and colleagues observed during the early stages of the COVID-19 pandemic [ 51 ]. Similarly, Geers and Coello [ 50 ] found that individuals higher in Germ Aversion preferred to keep a greater distance from individuals who were not wearing a face mask. Perhaps surprisingly, the Perceived Infectability dimension turned out not to be a significant predictor of preferred IPD.…”
Section: Discussionmentioning
confidence: 98%
“…The second dimension of the PVD scale, namely Germ Aversion, was considered slightly less relevant because it focuses more on individuals’ concerns about potential pathogen transmission from objects previously touched by other people rather than on direct interaction. However, a study conducted during the early phase of the COVID-19 pandemic [ 40 ] indicated that people with greater fear of being contaminated by pathogens (as indicated by the Germ Aversion dimension of the PVD scale) showed greater COVID-related changes in peripersonal space, which is a different, but potentially related concept to IPD [ 6 ] (but see [ 50 ]). Thus, Germ Aversion might also predict preferred IPD.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research on the BIS found that people responded with increased disgust to contagion cues, such as skin rashes or sneezes, and quite readily initiated avoidance behavior in situations of increased contagion risk (Gassen et al, 2018 ; Keller et al, 2022 ; Mortensen et al, 2010 ). A virtual reality study further observed that personal and interpersonal spaces were reduced with virtual characters wearing a face mask, especially in persons highly aversive to contagion risks (Geers & Coello, 2022 ). During the peak waves of the pandemic in 2020 and 2021, unmasked strangers, and even those without visible sickness cues, were most likely perceived as potentially contagious, given that even asymptomatic infections of COVID-19 are easily transmissible (Moghadas et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%